(untitled) (International Journal of Studies in Nursing, 2021)
Background: The present study emphasizes effective, quality, individualized and humanized care, in addition to reducing the wait for care in emergency rooms and reducing the costs of institutions providing health services. Objective: Identify how mobile applications can enable the provision of quality, fast and humanized nursing home care to the patient. Method: It is an integrative literature review, in which the Health Sciences Descriptors “biomedical technology”, “home care”, “nursing care” and “smartphone” were used, in the time frame between 2017 and 2020 in the databases PubMed Central data, Database in Nursing and Latin American and Caribbean Literature in Health Sciences. For the analysis, the Content Thematic was established. Results: Eleven studies were selected that met the eligibility criteria, resulting in the thematic categorization divided into: Development of applications for health care, assessment and education and Use of applications for health care. Conclusion: Assistance applications have their validity and importance, such as monitoring and welcoming the patient, as well as recording the patient’s history in each application, however, assistance at home prevents the patient’s displacement, waits in service queues, in addition to consist of individualized and humanized care, as valued by the holistic view that nursing and health professionals in general must have to provide healthcare.